Die tyd en ruimte in Eksodus 2. 'n Studie van die storie-aspekte in die narratiewe teks van Eksodus 2 (deel 2) - Brink, Aldert (Old Testament essays, 2003)
In part 1 of his study on the narrative in Exodus 2 the author explained that a narrative consists of three dimensions, that of story, text and narrator. In that article he concentrated on two aspects of the story dimension and their interrelation; that of events and characters. The focus of this article stays with the story dimension but concentrates on the aspects of time and space. The article explains the theory concerned with time and space and tests it on the text in Exodus 2. The study concludes that time and space are essential story ingredients for the reader to interpret the story.